Three-dimensional graphene composite material, lubricating oil and preparation method thereof

Porous reduced graphene oxide is prepared through high-pressure ultrasonic treatment and spray drying, and combined with carbon nanotubes to form a three-dimensional graphene composite material, solving the problem of graphene prone to agglomeration in lubricating oil and significantly improving the wear resistance and stability of lubricating oil.

CN117603749BActive Publication Date: 2025-04-15ZHONGRUN CHAOYOU (BEIJING) NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311171538.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-04-15
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

In the prior art, two-dimensional sheet graphene is prone to agglomeration in the lubricating oil system, resulting in limited effect on improving the frictional performance of the lubricating oil.

Method used

By mixing graphite oxide, the first strong acid, reducing agent and organic solvent, high-pressure ultrasonic treatment and spray drying, porous reduced graphene oxide was prepared, and mixed with the carbon nanotube solution was microwaved and lyophilized to form a three-dimensional graphene composite material wrapped with the carbon nanotube as the support framework.

Benefits of technology

It effectively avoids the agglomeration of graphene, improves the wear resistance of lubricating oil, reduces the friction coefficient and wear spot diameter, and improves the dispersion and stability of lubricating oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117603749B_ABST
    Figure CN117603749B_ABST
Patent Text Reader

Abstract

The present application relates to a three-dimensional graphene composite material, lubricating oil and a preparation method thereof. The preparation method of the three-dimensional graphene composite material comprises the following steps: after mixing graphite oxide, a first strong acid, a reducing agent and an organic solvent, the mixture is subjected to high-pressure ultrasonic treatment and spray drying in sequence to obtain porous reduced graphene oxide; after mixing a carbon nanotube mixed solution and porous reduced graphene oxide, the mixture is subjected to microwave treatment and a first freeze drying in sequence to obtain a three-dimensional graphene composite material; wherein the carbon nanotube mixed solution comprises carbon nanotubes, a surfactant and a solvent. Adding the three-dimensional graphene composite material obtained by the preparation method to lubricating oil can effectively reduce the friction coefficient and wear spot diameter of the lubricating oil, thereby effectively improving the anti-wear and friction-reducing performance of the lubricating oil, and at the same time, the obtained lubricating oil is evenly dispersed and has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and in particular to a three-dimensional graphene composite material, lubricating oil and a preparation method thereof. Background Art

[0002] Friction and wear are common in industrial production and daily life. The problems of mechanical loss and energy waste caused by them are becoming increasingly serious. According to statistics, nearly one-third of the annual energy loss is caused by friction of various mechanical equipment, and more than half of the failure of mechanical parts is caused by wear. Therefore, at a time when various industrial equipment is developing towards high precision and heavy load discovery, it is particularly important to develop new lubricants to effectively reduce mechanical friction and wear.

[0003] Graphene has shown great potential in the field of lubricant applications due to its excellent self-lubricating properties. However, ordinary two-dimensional graphene flakes tend to aggregate in lubricant systems, and it is also difficult to avoid graphene flake aggregation during the preparation of traditional three-dimensional graphene, resulting in limited improvement in the friction properties of lubricants. Summary of the invention

[0004] Based on this, the present application provides a three-dimensional graphene composite material, lubricating oil and a preparation method thereof that can effectively improve the anti-wear performance of lubricating oil.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] The first aspect of the present application provides a method for preparing a three-dimensional graphene composite material, comprising the following steps:

[0007] Mixing graphite oxide, a first strong acid, a reducing agent and an organic solvent, and sequentially subjecting the mixture to high pressure ultrasonic treatment and spray drying to obtain porous reduced graphene oxide; and

[0008] The carbon nanotube mixed solution and the porous reduced graphene oxide are mixed and then subjected to microwave treatment and a first freeze-drying in sequence to obtain the three-dimensional graphene composite material; wherein the carbon nanotube mixed solution comprises carbon nanotubes, a surfactant and a solvent.

[0009] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the conditions of the high-pressure ultrasonic treatment include: temperature 85°C~95°C, pressure 0.45 MPa~0.55 MPa, ultrasonic frequency 24 kHz~28 kHz, and treatment time 2 h~4 h.

[0010] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the spray drying conditions include: an inlet air temperature of 140° C. to 170° C., a feed flow rate of 200 mL / h to 300 mL / h, and a fan frequency of 30 Hz to 50 Hz.

[0011] In some of the embodiments, in the method for preparing the three-dimensional graphene composite material, the power of the microwave treatment is 1.0 kW-1.5 kW, and the time is 2 h~5 h.

[0012] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the first freeze-drying conditions include: vacuum degree 5 Pa to 25 Pa, condensation chamber temperature -65°C to -60°C, and drying time 18 h to 24 h.

[0013] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the pore size of the pore structure in the porous reduced graphene oxide is 100 nm to 200 nm.

[0014] In some of the embodiments, in the method for preparing the three-dimensional graphene composite material, the mass ratio of the carbon nanotubes to the porous reduced graphene oxide is (0.5~2):1.

[0015] In some embodiments, in the method for preparing a three-dimensional graphene composite material, the first strong acid includes concentrated nitric acid.

[0016] In some embodiments, in the method for preparing a three-dimensional graphene composite material, the reducing agent includes ascorbic acid.

[0017] In some embodiments, in the method for preparing a three-dimensional graphene composite material, the organic solvent includes toluene.

[0018] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the ratio of the mass of the graphite oxide, the mass of the reducing agent, and the volume of the first strong acid is 1 g: (0.2~0.8) g: (2~5) mL.

[0019] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the carbon nanotubes have an outer diameter of 6 nm to 13 nm and a length of 2.5 μm to 20 μm.

[0020] In some of the embodiments, in the method for preparing the three-dimensional graphene composite material, the surfactant includes at least one of hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate and polyisobutylene succinimide.

[0021] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, in the carbon nanotube mixed solution, the mass ratio of the carbon nanotubes to the surfactant is 1: (1-5).

[0022] In some embodiments, in the method for preparing the three-dimensional graphene composite material, the solvent includes water.

[0023] In some embodiments, in the method for preparing the three-dimensional graphene composite material, the preparation of the graphite oxide comprises the following steps:

[0024] The expanded graphite, the oxidant, the oxidation enhancer and the second strong acid are mixed and subjected to oxidation reaction to obtain a reaction solution;

[0025] The reaction solution is subjected to solid-liquid separation, and the solid phase is washed to neutrality and subjected to a second freeze-drying.

[0026] In some embodiments, in the method for preparing a three-dimensional graphene composite material, the oxidant includes potassium permanganate.

[0027] In some of the embodiments, in the method for preparing the three-dimensional graphene composite material, the oxidation enhancer includes at least one of potassium nitrate and sodium nitrate.

[0028] In some embodiments, in the method for preparing a three-dimensional graphene composite material, the second strong acid includes concentrated sulfuric acid.

[0029] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the expanded graphite has a sheet diameter of 5 to 10 microns, an expansion multiple of 400 to 600 times, and a specific surface area of ​​35 m 2 / g~50 m 2 / g.

[0030] In some of the embodiments, in the method for preparing the three-dimensional graphene composite material, the temperature of the oxidation reaction is 10°C to 20°C.

[0031] In some of the embodiments, in the method for preparing a three-dimensional graphene composite material, the second freeze-drying conditions include: vacuum degree 5 Pa to 25 Pa, condensation chamber temperature -65°C to -60°C, and drying time 18 h to 24 h.

[0032] The second aspect of the present application provides a three-dimensional graphene composite material, which is prepared by the preparation method of the three-dimensional graphene composite material provided by the first aspect.

[0033] A third aspect of the present application provides a lubricating oil, comprising a base oil and the three-dimensional graphene composite material provided in the second aspect.

[0034] In some of the embodiments, in the lubricating oil, the mass ratio of the three-dimensional graphene composite material to the base oil is (0.01~0.1):1.

[0035] The fourth aspect of the present application provides a method for preparing a lubricating oil, wherein the three-dimensional graphene composite material provided in the second aspect is uniformly mixed with an organic solvent to obtain a three-dimensional graphene composite material mixed liquid;

[0036] The three-dimensional graphene composite material mixed liquid is mixed with base oil.

[0037] In some of the embodiments, in the method for preparing lubricating oil, after the three-dimensional graphene composite material mixed liquid is mixed with the base oil, the mixed liquid is intercalated using a fluid accelerator, and the conditions of the intercalation treatment are: the treatment caliber is 2 cm~4 cm, the flow linear velocity is 10 m / s~20 m / s, and the treatment time is 1 h~4 h.

[0038] Compared with the prior art, the preparation method of the three-dimensional graphene composite material of the present application has the following beneficial effects:

[0039] The preparation method of the three-dimensional graphene composite material comprises the following steps: mixing graphite oxide with a first strong acid, a reducing agent and an organic solvent and then subjecting the mixture to high-pressure ultrasonic treatment, so that the graphite oxide is reduced and the exfoliation of the graphite oxide flakes is effectively promoted; and the graphite oxide is subjected to high-pressure ultrasonic treatment under the action of the first strong acid and the reducing agent, so that the reduced graphene oxide can be effectively pore-formed, thereby obtaining porous reduced graphene oxide, which has a large specific surface area and is conducive to the subsequent construction of a three-dimensional structure with carbon nanotubes; and spray drying the reaction solution after the high-pressure ultrasonic treatment can effectively avoid agglomeration between the porous reduced graphene oxides; and further the obtained porous reduced graphene oxide is subjected to high-pressure ultrasonic treatment. Graphene oxide is mixed with a carbon nanotube mixed solution including carbon nanotubes, a surfactant and a solvent and subjected to microwave treatment, and porous reduced graphene oxide is adsorbed and self-assembled on the carbon nanotubes in the carbon nanotube mixed solution to obtain a three-dimensional graphene composite material with carbon nanotubes as a supporting skeleton and porous reduced graphene oxide wrapped and covered on the carbon nanotube skeleton; the mixed solution after microwave treatment is first freeze-dried to effectively avoid agglomeration and accumulation of the porous reduced graphene oxide and the carbon nanotubes, and to enable the obtained three-dimensional graphene composite material to maintain a good three-dimensional structure, so that the three-dimensional graphene composite material has good dispersibility in lubricating oil, and can effectively improve the anti-wear performance of the lubricating oil.

[0040] Furthermore, adding the above three-dimensional graphene composite material to lubricating oil can effectively reduce the friction coefficient and wear spot diameter of the lubricating oil, thereby effectively improving the anti-wear and friction-reducing performance of the lubricating oil. At the same time, the obtained lubricating oil is evenly dispersed and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0042] Figure 1 This is a SEM image of the three-dimensional graphene composite material obtained in Example 1;

[0043] Figure 2 TEM image of the three-dimensional graphene composite material prepared in Example 1;

[0044] Figure 3 This is a physical picture of poly-alpha-olefin base oil;

[0045] Figure 4 This is a diagram showing the dispersion of the lubricating oil obtained in Example 1;

[0046] Figure 5 This is a diagram showing the dispersion of the lubricating oil obtained in Comparative Example 1. DETAILED DESCRIPTION

[0047] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0048] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0050] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0051] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0052] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0053] An embodiment of the present application provides a method for preparing a three-dimensional graphene composite material, comprising:

[0054] Step S10: mixing graphite oxide, a first strong acid, a reducing agent and an organic solvent, and then sequentially subjecting the mixture to high pressure ultrasonic treatment and spray drying to obtain porous reduced graphene oxide.

[0055] During the research process, the technicians of the present application found that in the absence of a reducing agent, the pore-forming effect is poor when the graphite oxide is mixed with the first strong acid and the organic solvent and then subjected to high-pressure ultrasonic treatment, and the generated graphene oxide is poorly dispersed in the organic solvent and the lubricating oil. Alternatively, when the reduced graphite oxide is mixed with the first strong acid and the organic solvent and then subjected to high-pressure ultrasonic treatment, no pores can be formed.

[0056] In the present application, graphite oxide is mixed with a first strong acid, a reducing agent and an organic solvent and then subjected to high-pressure ultrasonic treatment, so that the graphite oxide is reduced and the exfoliation of the graphite oxide flakes is effectively promoted. In addition, the graphite oxide is subjected to high-pressure ultrasonic treatment under the action of the first strong acid and the reducing agent, which can effectively form pores in the reduced graphene oxide after reduction, and has a large specific surface area, which is conducive to the subsequent formation of a three-dimensional structure with carbon nanotubes.

[0057] In some of the examples, in step S10, the conditions for high-pressure ultrasonic treatment include: temperature of 85°C to 95°C, pressure of 0.45 MPa to 0.55 MPa, ultrasonic frequency of 24 kHz to 28 kHz, and treatment time of 2 h to 4 h.

[0058] It can be understood that in high-pressure ultrasonic treatment, the temperature includes but is not limited to 85°C, 88°C, 90°C, 92°C, and 95°C; the pressure includes but is not limited to 0.45 MPa, 0.48 MPa, 0.50 MPa, 0.52 MPa, and 0.55 MPa; the ultrasonic frequency includes but is not limited to 24 kHz, 25 kHz, 26 kHz, and 28 kHz, and the treatment time includes but is not limited to 2 h, 2.5 h, 3 h, 3.5 h, and 4 h. In some examples, any two of these point values ​​may be used as end values ​​within a range, the same below.

[0059] In some of the examples, in step S10, high-pressure ultrasonic treatment is performed in a high-pressure ultrasonic reactor at 5 bar.

[0060] In some of the examples, in step S10, the spray drying conditions include: an inlet air temperature of 140° C. to 170° C., a feed flow rate of 200 mL / h to 300 mL / h, and a fan frequency of 30 Hz to 50 Hz.

[0061] It will be understood that the inlet air temperature includes but is not limited to 140°C, 150°C, 160°C, 165°C, and 170°C; the feed flow rate includes but is not limited to 200 mL / h, 220 mL / h, 250 mL / h, 280 mL / h, and 300 mL / h; and the fan frequency includes but is not limited to 30 Hz, 35 Hz, 40 Hz, 45 Hz, and 50 Hz.

[0062] In some of the examples, in step S10, the pore size of the pore structure in the porous reduced graphene oxide is 100 nm to 200 nm.

[0063] It can be understood that the pore size of the pore structure in the porous reduced graphene oxide includes but is not limited to 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, and 200 nm; in some examples, it can be within a range consisting of any two of these point values ​​as end values, the same below.

[0064] In some examples, in step S10, the first strong acid includes concentrated nitric acid.

[0065] In some examples, in step S10, the reducing agent includes ascorbic acid.

[0066] In some examples, in step S10 , the organic solvent includes toluene.

[0067] In some of the examples, in step S10, the ratio of the mass of graphite oxide, the mass of the reducing agent, and the volume of the first strong acid is 1 g: (0.2~0.8) g: (2~5) mL.

[0068] It can be understood that the mass ratio of graphite oxide to the mass of the reducing agent includes but is not limited to 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8; the ratio of the volume of the first strong acid to the mass of graphite oxide is 2 mL / g, 3 mL / g, 4 mL / g, 5 mL / g.

[0069] In some examples, in step S10, the preparation of graphite oxide includes the following steps:

[0070] Step S100: Mixing expanded graphite, an oxidant, an oxidation enhancer and a second strong acid and performing an oxidation reaction to obtain a reaction solution;

[0071] In some examples, in step S100 , the oxidant includes potassium permanganate.

[0072] In some examples, in step S100 , the oxidation enhancer includes at least one of potassium nitrate and sodium nitrate.

[0073] In some examples, in step S100, the second strong acid includes concentrated sulfuric acid.

[0074] In some of the examples, in step S100, the mass ratio of the oxidant, the oxidation enhancer, the second strong acid and the expanded graphite is (0.1-0.5):(0.3-0.8):(1-5):1.

[0075] It can be understood that the mass ratio of the oxidant to the expanded graphite includes but is not limited to 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1; the mass ratio of the oxidation enhancer to the expanded graphite includes but is not limited to 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1; the mass ratio of the second strong acid to the expanded graphite includes but is not limited to 1:1, 2:1, 3:1, 4:1, 5:1.

[0076] In some examples, in step S100, the mass ratio of the oxidant, the oxidation enhancer, the second strong acid and the expanded graphite is 0.3:0.5:3:1.

[0077] In some examples, in step S100, the expanded graphite has a sheet diameter of 5 to 10 μm, an expansion multiple of 400 to 600 times, and a specific surface area of ​​35 m 2 / g~50 m 2 / g.

[0078] It is understood that the diameter of the expanded graphite includes but is not limited to 5, 6, 7, 8, 9, 10 microns; the expansion multiple includes but is not limited to 400, 420, 450, 480, 500, 520, 550, 580, 600 times; the specific surface area includes but is not limited to 35 m 2 / g, 38 m 2 / g, 40 m 2 / g, 42 m 2 / g, 45 m 2 / g, 48 m 2 / g, 50 m 2 / g.

[0079] In some of the examples, in step S100, the oxidation reaction temperature is 10°C to 20°C, and the time is 2 h to 6 h.

[0080] It is understood that the temperature of the oxidation reaction includes but is not limited to 10°C, 12°C, 15°C, 18°C, and 20°C, and the time includes but is not limited to 2 h, 3 h, 4 h, 5 h, and 6 h.

[0081] Step S110: separating the reaction liquid into solid and liquid, washing the solid phase to neutrality and performing a second freeze-drying.

[0082] In some examples, in step S110 , the second freeze-drying includes vacuum freeze-drying.

[0083] In some of the examples, in step S110, the conditions for the second freeze-drying include: vacuum degree 5 Pa to 25 Pa, condensation chamber temperature -65°C to -60°C, and drying time 18 h to 24 h.

[0084] It can be understood that in the second freeze-drying, the vacuum degree includes but is not limited to 5 Pa, 10 Pa, 15 Pa, 20 Pa, 25 Pa, the condensation chamber temperature includes but is not limited to -65°C, -62°C, -64°C, -60°C, and the drying time includes but is not limited to 18 h, 20 h, 22 h, 24 h.

[0085] It can be understood that the methods of solid-liquid separation include but are not limited to filtration, suction filtration, centrifugation, etc.

[0086] In some of the examples, in step S110, the solid-liquid separation method is vacuum filtration.

[0087] In some examples, in step S110 , the washing solvent includes at least one of a NaOH solution and water.

[0088] Step S20: mixing the carbon nanotube mixed solution and the porous reduced graphene oxide, and then sequentially performing microwave treatment and a first freeze-drying to obtain a three-dimensional graphene composite material; wherein the carbon nanotube mixed solution includes carbon nanotubes, a surfactant and a solvent.

[0089] The preparation method of the three-dimensional graphene composite material comprises the following steps: mixing graphite oxide with a first strong acid, a reducing agent and an organic solvent and then subjecting the mixture to high-pressure ultrasonic treatment, so that the graphite oxide is reduced and the exfoliation of the graphite oxide flakes is effectively promoted; and the graphite oxide is subjected to high-pressure ultrasonic treatment under the action of the first strong acid and the reducing agent, so that the reduced graphene oxide can be effectively pore-formed, thereby obtaining porous reduced graphene oxide, and the porous reduced graphene oxide has a large specific surface area; and spray drying the reaction solution after the high-pressure ultrasonic treatment can effectively avoid agglomeration between the porous reduced graphene oxides; and further the obtained porous reduced graphene oxide is subjected to high-pressure ultrasonic treatment. Graphene is mixed with a carbon nanotube mixed solution including carbon nanotubes, a surfactant and a solvent and subjected to microwave treatment. The porous reduced graphene oxide is adsorbed and self-assembled with the carbon nanotubes in the carbon nanotube mixed solution to obtain a three-dimensional graphene composite material having the carbon nanotubes as a supporting skeleton and the porous reduced graphene oxide wrapped and covered on the carbon nanotube skeleton. The mixed solution after microwave treatment is first freeze-dried to effectively avoid agglomeration and accumulation of the porous reduced graphene oxide and the carbon nanotubes, and to enable the obtained three-dimensional graphene composite material to maintain a good three-dimensional structure, so that the three-dimensional graphene composite material has good dispersibility in lubricating oil.

[0090] It can be understood that the porous reduced graphene oxide is mainly distributed on the surface, and the carbon nanotubes are mainly distributed inside.

[0091] Furthermore, adding the above three-dimensional graphene composite material to lubricating oil can effectively reduce the friction coefficient and wear spot diameter of the lubricating oil, thereby effectively improving the anti-wear and friction-reducing performance of the lubricating oil. At the same time, the obtained lubricating oil is evenly dispersed and has good stability.

[0092] In some of the examples, in step S20, the power of the microwave treatment is 1.0 kW-1.5 kW, and the time is 2 h-5 h.

[0093] It is understood that the power of microwave treatment includes but is not limited to 1.0 kW, 1.1 kW, 1.2 kW, 1.3 kW, 1.4 kW, and 1.5 kW; and the time includes but is not limited to 2 h, 3 h, 4 h, and 5 h.

[0094] In some examples, in step S20, the first freeze-drying includes vacuum freeze-drying.

[0095] In some of the examples, in step S20, the conditions for the first freeze-drying include: vacuum degree 5 Pa to 25 Pa, condensation chamber temperature -65°C to -60°C, and drying time 18 h to 24 h.

[0096] It can be understood that in the first freeze-drying, the vacuum degree includes but is not limited to 5 Pa, 10 Pa, 15 Pa, 20 Pa, 25 Pa, the condensation chamber temperature includes but is not limited to -65°C, -62°C, -64°C, -60°C, and the drying time includes but is not limited to 18 h, 20 h, 22 h, 24 h.

[0097] In some of the examples, in step S20, the mass ratio of carbon nanotubes to porous reduced graphene oxide is (0.5-2):1.

[0098] It is understood that the mass ratio of carbon nanotubes to porous reduced graphene oxide includes but is not limited to 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, and 2:1.

[0099] In some of the examples, in step S20, the outer diameter of the carbon nanotube is 6 nm to 13 nm, and the length is 2.5 μm to 20 μm.

[0100] It can be understood that the outer diameter of the carbon nanotubes is 6 nm, 7 nm, 8 nm, 10 nm, 12 nm, and 13 nm, and the length is 2.5 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 16 μm, 18 μm, and 20 μm.

[0101] In some of the examples, in step S20, in the carbon nanotube mixed solution, the mass ratio of the carbon nanotubes to the surfactant is 1:(1-5).

[0102] It can be understood that the mass ratio of carbon nanotubes to surfactant includes but is not limited to 1:1, 1:2, 1:3, 1:4, and 1:5.

[0103] It will be appreciated that surfactants include, but are not limited to, anionic surfactants, cationic surfactants, and zwitterionic surfactants.

[0104] In some examples, in step S20, the surfactant includes an anionic surfactant and a cationic surfactant.

[0105] In some examples, in step S20, the surfactant includes at least one of cetyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, and polyisobutylene succinimide.

[0106] In some examples, in step S20, the surfactant includes hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, and polyisobutylene succinimide.

[0107] In some examples, in step S20 , the solvent includes water.

[0108] In some examples, in step S20, the preparation of the carbon nanotube mixed solution includes:

[0109] Step S200: mixing carbon nanotubes, surfactant and solvent and subjecting them to high-pressure ultrasonic treatment.

[0110] In some of the examples, in step S200, the conditions for high-pressure ultrasonic treatment include: temperature of 85°C to 95°C, pressure of 0.45 MPa to 0.55 MPa, ultrasonic frequency of 24 kHz to 28 kHz, and treatment time of 2 h to 4 h.

[0111] It can be understood that in high-pressure ultrasonic treatment, the temperature includes but is not limited to 85°C, 88°C, 90°C, 92°C, and 95°C, the pressure includes but is not limited to 0.45 MPa, 0.48 MPa, 0.50 MPa, 0.52 MPa, and 0.55 MPa, the ultrasonic frequency includes but is not limited to 24 kHz, 25 kHz, 26 kHz, 27 kHz, and 28 kHz, and the treatment time includes but is not limited to 2 h, 3 h, and 4 h.

[0112] One embodiment of the present application provides a three-dimensional graphene composite material, which is prepared using the above-mentioned method for preparing the three-dimensional graphene composite material.

[0113] One embodiment of the present application provides the use of the above three-dimensional graphene composite material in the preparation of lubricating oil.

[0114] An embodiment of the present application provides a lubricating oil, comprising a base oil and the above-mentioned three-dimensional graphene composite material.

[0115] Adding the above three-dimensional graphene composite material to lubricating oil can effectively reduce the friction coefficient and wear spot diameter of the lubricating oil, thereby effectively improving the anti-wear and friction-reducing properties of the lubricating oil. At the same time, the obtained lubricating oil is evenly dispersed and has good stability.

[0116] In some of these examples, the mass ratio of three-dimensional graphene composite material to base oil in the lubricating oil is (0.01~0.1):1.

[0117] It can be understood that the mass ratio of the three-dimensional graphene composite material to the base oil includes but is not limited to 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.08:1, and 0.1:1.

[0118] Optionally, the mass ratio of the three-dimensional graphene composite material to the base oil is (0.02~0.03):1.

[0119] It is understood that the present application does not limit the type of base oil.

[0120] In some of the examples, in the lubricating oil, the base oil includes at least one of a poly-alpha-olefin base oil, an ester base oil, and a silicone oil.

[0121] In some of these examples, the lubricating oil also includes an organic solvent.

[0122] Some of these examples include N-methylpyrrolidone (NMP) in lubricating oils.

[0123] In some of these examples, the mass ratio of organic solvent to three-dimensional graphene composite material in lubricating oil is (1~3):1.

[0124] It can be understood that the mass ratio of the organic solvent to the three-dimensional graphene composite material includes but is not limited to 1:1, 2:1, and 3:1.

[0125] An embodiment of the present application provides a method for preparing a lubricating oil, comprising:

[0126] Step S30: uniformly mixing the three-dimensional graphene composite material and the organic solvent to obtain a three-dimensional graphene composite material mixed solution.

[0127] In some of the examples, in step S30, the three-dimensional graphene composite material is mixed with the organic solvent and then treated in a vortex mixer at 5000-8000 r / min for 10 min-20 min to be uniformly mixed.

[0128] Step S40: mixing the three-dimensional graphene composite material mixed liquid with the base oil.

[0129] By first uniformly mixing the three-dimensional graphene composite material with an organic solvent and then adding the obtained three-dimensional graphene composite material mixed liquid into the base oil, the anti-wear and friction-reducing performance of the lubricating oil can be further improved.

[0130] In some of the embodiments, in step S40, after the three-dimensional graphene composite material mixed liquid is mixed with the base oil, the mixed liquid is intercalated using a fluid accelerator, and the conditions of the intercalation treatment are: the treatment caliber is 2 cm~4 cm, the flow linear velocity is 10 m / s~20 m / s, and the treatment time is 1 h~4 h.

[0131] It is understood that the processing diameter includes but is not limited to 2 cm, 3 cm, and 4 cm, the flow linear speed includes but is not limited to 10 m / s, 12 m / s, 15 m / s, 18 m / s, and 20 m / s, and the processing time includes but is not limited to 1 h, 2 h, 3 h, and 4 h.

[0132] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0133] Example 1

[0134] (1) Expanded graphite, flake diameter 5 μm, expansion multiple 400 times, specific surface area 35 m 2 / g, for every 100g of the above expanded graphite, 300mL of concentrated H2SO4, 50g of potassium nitrate and 30g of potassium permanganate were used, the temperature was controlled at 20℃ and stirred for 4h, then vacuum filtered, filtered and washed with NaOH and deionized water until neutral, and vacuum freeze-dried to obtain graphite oxide; wherein, the vacuum freeze-drying conditions are: vacuum degree 5 Pa, condensation chamber temperature -65℃, drying time 18h;

[0135] (2) 100 g of graphite oxide, 1000 mL of toluene, 300 mL of concentrated nitric acid, and 50 g of ascorbic acid were mixed, and then oscillated for 3 h in a high-pressure ultrasonic reactor at 5 bar using a high-pressure ultrasonic device. The porous reduced graphene oxide was obtained by spray drying. The conditions for high-pressure ultrasonic treatment were: temperature 85 °C, pressure 0.45 MPa, ultrasonic frequency 24 kHz, and treatment time 2 h. The conditions for spray drying were: inlet air temperature 140 °C, feed flow rate 200 mL / h, and fan frequency 30 Hz. The pore size of the pore structure in the porous reduced graphene oxide was 100 nm, and the specific surface area was 500 m 2 / g;

[0136] (3) Multi-walled carbon nanotubes (outer diameter × length = 6 nm × 2.5 μm): 10 g of multi-walled carbon nanotubes, 10 g of cationic hexadecyltrimethylammonium bromide (CTAB), 5 g of anionic sodium dodecylbenzene sulfonate (SD-BS), and 3 g of polyisobutylene succinimide were dissolved in 1000 mL of deionized water, and the mixture was oscillated in a high-pressure ultrasonic reactor at 5 bar for 3 hours using an ultrasonic device to obtain a carbon nanotube mixed solution;

[0137] (4) The porous reduced graphene oxide and carbon nanotube mixed solution were mixed in a mass ratio of 1:1, treated with a microwave high pressure reactor at a power of 1.0 kW for 3 h, and vacuum freeze-dried for 5 h to obtain a three-dimensional graphene composite material; wherein the vacuum freeze-drying conditions are: vacuum degree 5 Pa, condensation chamber temperature -65 ° C, and drying time 18 h; the SEM image of the three-dimensional graphene composite material is shown in Figure 1 As shown, the TEM image of the three-dimensional graphene composite material is Figure 2 As shown. Figure 1 It can be seen that the surface of the three-dimensional carbon material is mainly graphene sheets, and there is no distribution of carbon nanotubes on the surface; Figure 2 It can be seen that in the three-dimensional graphene composite material, the carbon nanotubes CNT serve as a skeleton support structure inside, while the reduced graphene oxide RGO is assembled around the carbon nanotubes.

[0138] (5) treating 10 g of the three-dimensional graphene composite material with 20 g of N-methylpyrrolidone (NMP) in a vortex mixer at 5000 rpm for 10 min to obtain a three-dimensional graphene composite material mixed solution;

[0139] (6) The three-dimensional graphene composite material mixture and the poly-α-olefin base oil were mixed in a mass ratio of 0.02:1, and a fluid accelerator was used to perform a fluid high-speed differential interlayer motion treatment (i.e., intercalation treatment) with a treatment aperture of 2 cm and a flow linear velocity of 10 m / s for 1 h to obtain a lubricating oil.

[0140] Example 2

[0141] The method is basically the same as Example 1, except that the expanded graphite in step (1) of Example 2 has a sheet diameter of 10 μm, an expansion multiple of 600 times, and a specific surface area of ​​50 m 2 / g.

[0142] Example 3

[0143] The method is basically the same as Example 1, except that the multi-walled carbon nanotubes in step (3) of Example 3 have an outer diameter × length = 13 nm × 20 μm.

[0144] Example 4

[0145] The method is basically the same as Example 1, except that the microwave treatment power in step (4) of Example 4 is 1.5 kW.

[0146] Example 5

[0147] The method is basically the same as Example 1, except that in step (5) of Example 5, 10 g of the three-dimensional graphene composite material is treated with 20 g of N-methylpyrrolidone (NMP) in a vortex mixer at 8000 rpm for 20 min.

[0148] Example 6

[0149] The method is basically the same as Example 1, except that in step (6) of Example 6, the mass ratio of the three-dimensional graphene composite material to the poly-α-olefin base oil is 0.03:1, and the conditions of the intercalation treatment are: treatment diameter 4 cm, flow linear velocity 20 m / s, and treatment time 4 h.

[0150] Example 7

[0151] The method is basically the same as Example 1, except that in step (4) of Example 7, the mass ratio of porous reduced graphene oxide to carbon nanotubes is 2:1.

[0152] Comparative Example 1

[0153] The method is basically the same as Example 1, except that steps (1) and (2) are omitted, and the porous reduced graphene oxide in step (4) of Example 1 is replaced by expanded graphite of the same mass, with a sheet diameter of 5 μm, an expansion multiple of 400 times, and a specific surface area of ​​35 m 2 / g.

[0154] Comparative Example 2

[0155] The method is basically the same as Example 1, except that in step (3) of Comparative Example 2, no surfactant is added, and 10 g of multi-walled carbon nanotubes are directly dissolved in 1000 mL of deionized water, and the mixture is oscillated in a high-pressure ultrasonic reactor at 5 bar for 3 hours using an ultrasonic device to obtain a carbon nanotube mixed solution.

[0156] Comparative Example 3

[0157] The method is basically the same as Example 1, except that in step (4) of Comparative Example 3, the mixed solution of porous reduced graphene oxide and carbon nanotubes is ultrasonically treated for 3 h at normal pressure and vacuum-heated and dried for 5 h at 60°C.

[0158] Comparative Example 4

[0159] The method is basically the same as Example 1, except that in step (2) of Comparative Example 4, concentrated nitric acid is not added.

[0160] Comparative Example 5

[0161] The method is basically the same as Example 1, except that steps (1) and (2) are omitted in Example 5, and the porous reduced graphene oxide in step (4) of Example 1 is replaced by commercially available reduced graphene oxide (Changzhou Sixth Element Materials Technology Co., Ltd.) of equal mass, with a specific surface area of ​​450-550 m 2 / g.

[0162] The friction coefficient of the lubricating oils prepared in the examples and comparative examples was tested according to ASTM D5183-95, the wear spot diameter was tested according to SH / T 0204-92 lubricating grease anti-wear performance test method (four-ball machine method), and the extreme pressure performance of the lubricating oil (maximum no-seizure load P B )Tested in accordance with GB / T 3142-1982 standard, maximum no-seizure load P B The larger the value, the better the lubrication performance of the lubricant. The results are shown in Table 1.

[0163] Table 1

[0164]

[0165] Among them, after standing for 90 days, poly-alpha-olefin base oil such as Figure 3As shown, the dispersion of the lubricating oil obtained in Example 1 is as follows Figure 4 As shown, the dispersion of the lubricating oil obtained in Comparative Example 1 is as follows Figure 5 shown.

[0166] From Table 1 and Figures 3-5 It can be seen that compared with the comparative example and the poly-α-olefin base oil, the friction coefficient and the wear spot diameter of the lubricating oil prepared in the embodiment are significantly reduced, indicating that the anti-wear and friction-reducing performance of the lubricating oil is improved. At the same time, the lubricating oil is evenly dispersed and has good stability.

[0167] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0168] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A method for preparing a three-dimensional graphene composite material, characterized in that: The following steps are involved: Mixing graphite oxide, a first strong acid, a reducing agent and an organic solvent, and sequentially subjecting the mixture to high pressure ultrasonic treatment and spray drying to obtain porous reduced graphene oxide; and The carbon nanotube mixed solution and the porous reduced graphene oxide are mixed and then subjected to microwave treatment and a first freeze-drying in sequence to obtain the three-dimensional graphene composite material; wherein the carbon nanotube mixed solution comprises carbon nanotubes, a surfactant and a solvent.

2. The preparation method according to claim 1, characterized in that The preparation method has at least one of the following characteristics (1) to (2): (1) The conditions of the high-pressure ultrasonic treatment include: temperature of 85°C to 95°C, pressure of 0.45 MPa to 0.55 MPa, ultrasonic frequency of 24 kHz to 28 kHz, and treatment time of 2 h to 4 h; (2) The spray drying conditions include: inlet air temperature of 140°C to 170°C, feed flow rate of 200 mL / h to 300 mL / h, and fan frequency of 30 Hz to 50 Hz.

3. The preparation method according to claim 1, characterized in that: The preparation method has at least one of the following characteristics (1) to (2): (1) The power of the microwave treatment is 1.0 kW-1.5 kW, and the time is 2 h-5 h; (2) The first freeze-drying conditions include: vacuum degree 5 Pa ~ 25 Pa, condensation chamber temperature -65 ° C ~ -60 ° C, and drying time 18 h ~ 24 h.

4. The preparation method according to claim 1, characterized in that: The pore size of the pore structure in the porous reduced graphene oxide is 100 nm to 200 nm.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon nanotubes to the porous reduced graphene oxide is (0.5-2):

1.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method has at least one of the following characteristics (1) to (4): (1) the first strong acid comprises at least one of concentrated nitric acid, phosphoric acid and perchloric acid; (2) the reducing agent comprises at least one of ascorbic acid, oxalic acid and glyoxylic acid; (3) The organic solvent includes at least one of toluene, xylene and tetramethylbenzene; (4) The ratio of the mass of the graphite oxide, the mass of the reducing agent and the volume of the first strong acid is 1 g: (0.2~0.8) g: (2~5) mL.

7. The preparation method according to any one of claims 1 to 5, characterized in that The preparation method has at least one of the following characteristics (1) to (4): (1) The outer diameter of the carbon nanotube is 6 nm to 13 nm, and the length is 2.5 μm to 20 μm; (2) the surfactant comprises at least one of cetyltrimethylammonium bromide, sodium dodecylbenzene sulfonate and polyisobutylene succinimide; (3) In the carbon nanotube mixed solution, the mass ratio of the carbon nanotube to the surfactant is 1: (1-5); (4) The solvent includes water.

8. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation of the graphite oxide comprises the following steps: The expanded graphite, the oxidant, the oxidation enhancer and the second strong acid are mixed and subjected to oxidation reaction to obtain a reaction solution; The reaction solution is subjected to solid-liquid separation, and the solid phase is washed to neutrality and subjected to a second freeze-drying.

9. The preparation method according to claim 8, characterized in that: The preparation step of the graphite oxide has at least one of the following characteristics (1) to (6): (1) The oxidant comprises potassium permanganate; (2) The oxidation enhancer includes at least one of potassium nitrate and sodium nitrate; (3) the second strong acid comprises concentrated sulfuric acid; (4) The expanded graphite has a sheet diameter of 5 μm to 10 μm, an expansion multiple of 400 to 600 times, and a specific surface area of ​​35 m 2 / g~50m 2 / g; (5) The temperature of the oxidation reaction is 10°C to 20°C; (6) The conditions of the second freeze-drying process include: vacuum degree 5 Pa to 25 Pa, condensation chamber temperature -65°C to -60°C, and drying time 18 h to 24 h.

10. A three-dimensional graphene composite material, characterized in that: The method is described in any one of claims 1 to 9.

11. A lubricating oil, characterized in that: The method comprises a base oil and the three-dimensional graphene composite material as claimed in claim 10.

12. The lubricating oil according to claim 11, characterized in that The mass ratio of the three-dimensional graphene composite material to the base oil is (0.01-0.1):

1.

13. A method for preparing lubricating oil, characterized in that: The following steps are involved: Evenly mixing the three-dimensional graphene composite material according to claim 10 with an organic solvent to obtain a three-dimensional graphene composite material mixed solution; The three-dimensional graphene composite material mixed liquid is mixed with base oil.

14. The preparation method according to claim 13, characterized in that: After the three-dimensional graphene composite material mixed liquid is mixed with the base oil, a fluid accelerator is used to perform intercalation treatment on the mixed liquid, and the conditions of the intercalation treatment include: a treatment caliber of 2 cm to 4 cm, a flow linear velocity of 10 m / s to 20 m / s, and a treatment time of 1 h to 4 h.

Citation Information

Patent Citations

  • Preparation method and application of porous graphene-based composite film material

    CN110600277A

  • Preparation method of graphene / carbon nanotube composite aerogel

    CN112876201A